1996
DOI: 10.2134/jeq1996.00472425002500040024x
|View full text |Cite
|
Sign up to set email alerts
|

DDT Persistence and Volatility as Affected by Management Practices after 23 Years

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…These findings are consistent with previous results from our research group (Feist et al 2005), where DDE was the primary chlorinated contaminant detected in Lower Columbia River white sturgeon gonads and livers (the same fish we obtained blood plasma samples from). The greater concentration of DDE over DDD, and DDT in our study and by Feist et al (2005), suggests that the source of DDE is from agricultural runoff, since environmental degradation of DDT into primarily DDE involves aerobic pathways (Spencer et al 1996). Although plasma samples were analyzed for 17 OC pesticides, we statistically analyzed only the P DDT (DDE + DDD + DDT), since only DDE and DDD were measured in all samples above the detection limit and made up the majority of the total plasma pesticide burden.…”
Section: Resultsmentioning
confidence: 57%
“…These findings are consistent with previous results from our research group (Feist et al 2005), where DDE was the primary chlorinated contaminant detected in Lower Columbia River white sturgeon gonads and livers (the same fish we obtained blood plasma samples from). The greater concentration of DDE over DDD, and DDT in our study and by Feist et al (2005), suggests that the source of DDE is from agricultural runoff, since environmental degradation of DDT into primarily DDE involves aerobic pathways (Spencer et al 1996). Although plasma samples were analyzed for 17 OC pesticides, we statistically analyzed only the P DDT (DDE + DDD + DDT), since only DDE and DDD were measured in all samples above the detection limit and made up the majority of the total plasma pesticide burden.…”
Section: Resultsmentioning
confidence: 57%
“…Spencer et al (1996) found a maximum ΣDDT concentration of 4800 ng g -1 in agricultural soils in California. Dimond and Owen (1996) reported a maximum ΣDDT concentration in Maine forest soils of 1898 ng g -1 .…”
Section: Persistence Of Ddt At Point Peleementioning
confidence: 95%
“…The compound DDT (dichloro-diphenyl-trichloroethane) degrades along two principal degradation pathways; DDT degrades to DDE (dichloro-diphenyl-dichloroethylene) by dechlorination in aerobic soils and DDT degrades to DDD (dichloro-diphenyl-dichloroethane) by reductive dechlorination in anaerobic or flooded soil (Guenzi and Beard 1968;Guenzi et al 1971;Farmer et al 1974;Aislabie et al 1997;Boul et al 1994;Spencer et al 1996). The half-life for the transformation of DDT to DDE under aerobic conditions and in temperate soils varies due to soil temperature, moisture content, and organic carbon content.…”
mentioning
confidence: 99%
“…Residue levels of organochlorine pesticides are affected by application history, agricultural practices, soil phys- ico-chemical properties, as well as physico-chemical properties of agrochemicals and meteorological factors such as temperature and rainfall etc. (Szeto and Price, 1991;Boul et al, 1994;Spencer et al, 1996). OCPs are hydrophobic and considered to be easily adsorbed by soil organic matter.…”
Section: Factors Affecting Residue Levelsmentioning
confidence: 99%